1998
DOI: 10.1177/002215549804600706
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Deoxyribonuclease I Along the Secretory Pathway in Paneth Cells of Human Small Intestine

Abstract: SUMMARYThe expression and distribution of deoxyribonuclease I (DNase I) in human duodenum, jejunum and ileum were examined by DNase I activity assay and the reverse transcriptase-polymerase chain reaction (RT-PCR), immunofluorescence, in situ hybridization, and immunocytochemical ultrastructural analyses. High levels of DNase I were detected in the cytoplasm of Paneth cells in human small intestine. A tissue homogenate fraction rich in Paneth cells showed strong DNase I-specific enzymatic activity. Immunofluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 37 publications
0
20
1
Order By: Relevance
“…Recently, it has been suggested that the peripheral halo mainly contains O-linked oligosaccharides with N-acetyl-galactosamine (GalNAc) and N-acetyl-d-glucosamine (GlcNAc) residues and N-linked oligosaccharides with GlcNAc residues (33). The peripheral Pc halo also contains the antimicrobial DNase I that is specifically associated with the exocrine secretory granules (34). The characteristic peripheral intermediately dense halo ( Figure 6E, left panel, arrow) characteristic of WT animals was completely absent in the Pc granules of germ-free Cd1d -/-mice and instead an "empty" halo remained ( Figure 6E, right panel, arrow).…”
Section: Figurementioning
confidence: 99%
“…Recently, it has been suggested that the peripheral halo mainly contains O-linked oligosaccharides with N-acetyl-galactosamine (GalNAc) and N-acetyl-d-glucosamine (GlcNAc) residues and N-linked oligosaccharides with GlcNAc residues (33). The peripheral Pc halo also contains the antimicrobial DNase I that is specifically associated with the exocrine secretory granules (34). The characteristic peripheral intermediately dense halo ( Figure 6E, left panel, arrow) characteristic of WT animals was completely absent in the Pc granules of germ-free Cd1d -/-mice and instead an "empty" halo remained ( Figure 6E, right panel, arrow).…”
Section: Figurementioning
confidence: 99%
“…During chronic pancreatitis, after pancreatic duct ligation in hamsters and in diabetic mice, PCs become hyperplastic [128 -131]. Considering that pancreatic lipase-related protein 2 [121], pancreatic carboxylesterase [125], phospholipase B/lipase [132], and DNAse I [133] have been localized in PCs, PC secretions may have digestive functions in small intestinal regions distant from the pancreas, where digestive enzymes originating from the pancreas may have undergone autodegradation and degradation through microbial products. However, several other digestive enzymes including chymotrypsin, amylase, and lipase are reportedly not expressed in the small intestine [134].…”
Section: Relationship Of Pcs To Pancreatic Cellsmentioning
confidence: 99%
“…The function of DNases within the small intestine is debated and very few researchers purified DNases from small intestine. DNase I was purified and studied from human small intestine in 1998 [13], while the present work purified a DNase II from the lysosomes of jejunum of the small intestine in human. The authors used two methods for the purification of the enzyme: a classical method that used affinity chromatography and the immunoabsorption technique [14].…”
Section: Introductionmentioning
confidence: 99%